Seroprevalence and associated risk factors of avian influenza virus subtype H9N2 in backyard poultry of Peshawar Pakistan - Rehman, S.; Khan, M. I.; Rantam, F. A.; Effendi, M. H.; Shehzad, A.; Tariq, A. (Diponegoro University, 2021)
The current study was conducted to estimate the serological prevalence and risk factors associated with the transmission of avian influenza subtype H9N2 among backyard poultry from different villages of semi-arid climate district Peshawar Pakistan between January to May 2019. In total, 240 blood samples of healthy backyard poultry older than two months were collected from 30 different villages of district Peshawar. A predesigned questionnaire was used to collect the data related to risk factors. Se-rum samples were tested through the haemagglutination inhibition (HI) test further confirmed by the micro-neutralizing test (MN). Antibody body titer ≤ 8 considered negative for prevalence of H9N2. In order to classify risk factors, Chi-square and Logistic regression analyses were performed. Out of 240, 150 were found to be positive. The overall seroprevalence was 62.5%, mean antibody titer for avian influenza virus in all villages was 6.8 and (95%) confidence interval ranges from 35.33 to 51.70% re-spectively. The high prevalence of antibodies to avian influenza viruses in bird serum emphasizes that avian influenza plays an important role in the respiratory infections of backyard chickens in the area, and possibly throughout Pakistan. In order to avoid the introduction of H9N2, biosecurity initiatives, surveillance, monitoring systems, and to some extent, vaccinations are useful tools.